Aeródromos públicos e privados: os bens utilizados e cedidos aos particulares - Muraro, Igor Santos (2017)
It is inteded, through this work, investigate the legal status of goods assigned to public and private airports, and all the activities that Federal Law 7.565/1986, the normative acts of ANAC and the concessions contracts of the airports, allow them to coexist in these areas. To do so, we first look at the concept of public areas, as well as its modality of use by individuals. Once this is done, we’ll turn our attention to private and public airports, as well as the kind of activities that the law allows to be performed in these areas, in order to verify the private or public nature of each one. Finally, under these premises, we identify the legal regime of the assets of privet airports, as well as those located at public airports, but ceded to private individual for their exploration